A Introduction to the role of civil engineering in infrastructure development for students of SMAN 3 Jakarta - Liana Herlina; Endah Kurniyaningrum; Aksan Kawanda; Larasati Rizky Putri; Imas Widhah Misshuari (Universitas Muhammadiyah Magelang, 2025)
Infrastructure development in Indonesia requires many civil engineering graduates, who play an important role in developing sustainable infrastructure to meet current needs. Based on data from the Central Statistics Agency (BPS) in 2023, the Net Participation Rate (APM) for the 19-24 age group reached 20.63% for higher education, including both undergraduate and diploma programs. To support this development, the Community Service Team of the Faculty of Civil Engineering collaborated with SMA Negeri 3 Jakarta to organize an activity to introduce the role of civil engineering in infrastructure development. This activity aims to familiarize students with the role of civil engineering and assist them in exploring their interests and talents in this field. The method of implementing the activity includes delivering materials, demonstrating equipment in the laboratory, and conducting a questionnaire session to determine the level of student understanding. The results showed that the level of student understanding of civil engineering reached 42% in the